MSMEs envisaged as the economy spearhead for Bali in the covid-19 pandemic situation - Nyoman Sri Subawa; Ni Wayan Widhiasthini; Ni Putu Intan Permatasari; Ni Nyoman Sri Wisudawati (Cogent Economics & Finance, 2022)
As a region that relies on the tourism sector as the priority then, when the Covid-19 pandemic hit the world, Bali became one of the most affected regions. Efforts are being made to drive the MSME sector in overcoming the financial crisis. The problem discussed was how the impact of MSMEs as the economy spearhead in the Covid-19 pandemic situation. The urgency of this research is to contribute to the practice of community empowerment through the MSME sector. The research method used is a qualitative method with a case study approach, to explore and comprehensively describe the phenomena that occurred in the MSME sector. This research was conducted in Bali Province, the determination of informants was carried out purposively. The results showed that MSMEs had become the economy spearheaded during the pandemic, become a solution to economic growth, accommodated the process of quadrant shifting from tourism performer into MSME performer, implemented economy digitization at various stages, and business activities. The sharing economy pattern has been formed in MSME business practices, through various related business sectors. The findings of this study are (1) a change in the mindset of the people who initially had a mentality as workers, now have an entrepreneurial spirit, and (2) the application of the sharing economy as an exchange of values in the MSME sector. The limitation of the research is that the research location is only in one area. The social implication is that MSME becomes a solution to prevent the potential social vulnerability.
Keywords: 330; MSME; digital economy; related business sector; sharing economy; tourism performer; economy spearhead